2017
DOI: 10.1111/jfpe.12576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of encapsulation techniques on the structure, physical properties, and thermal stability of fish oil microcapsules by spray drying

Abstract: The physical properties and thermal stability of gelatin/gum‐Arabic microcapsules loaded fish oil, developed by various encapsulation techniques such as directly spray‐dried microcapsule, complex coacervation microcapsule, and double‐encapsulated microcapsule (DEM) were investigated. All the particles dried by spray drying and evaluated by scanning electron microscopy (SEM), thermal analysis, cumulative release analysis, and rheological measurements. The external and internal core–shell structure of microcapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
(38 reference statements)
0
18
0
1
Order By: Relevance
“…Microencapsulation of plant‐derived bioactive compounds has attracted industrial and scientific community interest as valuable alternatives to protect phytochemicals against deleterious processing and environmental conditions, facilitating their technological incorporation into food and pharmaceutical preparations (Yu et al . ; Belščak‐Cvitanović et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation of plant‐derived bioactive compounds has attracted industrial and scientific community interest as valuable alternatives to protect phytochemicals against deleterious processing and environmental conditions, facilitating their technological incorporation into food and pharmaceutical preparations (Yu et al . ; Belščak‐Cvitanović et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A schematic image from the internal structure diagram of edible oil‐loaded microcapsules prepared with (A) emulsion‐based spray drying, (B) complex coacervation and (C) DE‐EG methods (Adapted from Yu and others ).…”
Section: Current Microencapsulation Techniques By Tgase Crosslinkingmentioning
confidence: 99%
“…In addition, the emulsion instability because of the creation of intermittent oil deposits during freeze drying can considerably reduce the EE (Anwar and Kunz ). Yu and others () have currently investigated the impact of various encapsulation techniques on the EE of fish oil microcapsules. They concluded that microcapsules produced by DE‐EG method had higher EE level (93.71%) as a result of the second embedding, than those prepared by complex coacervation (89.78%) and emulsion‐based spray drying (86.9%) techniques.…”
Section: Physical Characteristics Of Tgase‐crosslinked Microcapsulesmentioning
confidence: 99%
See 2 more Smart Citations